2003
DOI: 10.1038/sj.onc.1206376
|View full text |Cite
|
Sign up to set email alerts
|

The adenovirus E1A oncoprotein recruits the cellular TRRAP/GCN5 histone acetyltransferase complex

Abstract: The adenovirus E1A oncoprotein stimulates cell growth and inhibits differentiation by deregulating the normal transcription program via interaction with positive and negative cellular effectors. E1A associates with transcriptional regulatory complexes containing p400 and TRRAP involved in chromatin remodeling and decondensation. TRRAP is a component of three distinct human histone acetyltransferase (HAT) complexes: the TIP60 complex and complexes containing GCN5 or PCAF. We demonstrate here that E1A binds a TR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 29 publications
7
72
0
Order By: Relevance
“…These include c-Myc, p53, E2F1, E2F4, E1A, ERa, ERb, VDR, PPARg, LXR, FXR, b-catenin, Skp1 and BRCA1 Lang et al, 2001;Park et al, 2001;Ard et al, 2002;Yanagisawa et al, 2002;Lang and Hearing, 2003;Unno et al, 2005;Cheng et al, 2006;Oishi et al, 2006;Sierra et al, 2006;Finkbeiner and Herceg, unpublished results). Interestingly, the TRRAP domains that interact with diverse partners are not overlapping and it can be speculated that TRRAP may serve not only as a scaffold for HAT complexes but also as a platform for recruitment of different regulatory factors and complexes to chromatin.…”
Section: Cellular Pools Of Trrapmentioning
confidence: 91%
See 1 more Smart Citation
“…These include c-Myc, p53, E2F1, E2F4, E1A, ERa, ERb, VDR, PPARg, LXR, FXR, b-catenin, Skp1 and BRCA1 Lang et al, 2001;Park et al, 2001;Ard et al, 2002;Yanagisawa et al, 2002;Lang and Hearing, 2003;Unno et al, 2005;Cheng et al, 2006;Oishi et al, 2006;Sierra et al, 2006;Finkbeiner and Herceg, unpublished results). Interestingly, the TRRAP domains that interact with diverse partners are not overlapping and it can be speculated that TRRAP may serve not only as a scaffold for HAT complexes but also as a platform for recruitment of different regulatory factors and complexes to chromatin.…”
Section: Cellular Pools Of Trrapmentioning
confidence: 91%
“…The evidence that simultaneous enrichment of TRRAP, transcription factors and HATs at chromatin is associated with promoter-specific chromatin hyperacetylation Bouchard et al, 2001;Frank et al, 2001;Herceg et al, 2003;Li et al, 2004;Taubert et al, 2004) led to the suggestion that TRRAP functions to recruit HAT complexes to transcription factors bound to their target promoters in chromatin. TRRAP was found as a target of the adenovirus E1A oncoprotein and to be important for oncogenic transformation mediated by viral oncoproteins Deleu et al, 2001;Lang et al, 2001;Lang and Hearing, 2003). We have recently shown that Trrap is involved in the repair of DNA double-strand breaks (DSBs) , indicating that the function of TRRAP and TRRAP-mediated histone acetylation is not limited to transcriptional control, but likely extents to all chromatin-based processes that use DNA as a template.…”
Section: Introductionmentioning
confidence: 99%
“…Like Tip60 itself, the NuA4 subunits BAF53a, TRRAP and p400 have been implicated in c-Myc oncogene-mediated cellular transformation (Fuchs et al, 2001;Nikiforov et al, 2002;Park et al, 2002). Both TRRAP and p400 are also targeted by the adenoviral E1A oncoprotein and are essential for E1A-mediated cellular transformation (Fuchs et al, 2001;Lang and Hearing, 2003). Although the adenovirus is not associated with human malignancy, this evidence implies that TRRAP and p400 play key roles in cellular regulation and can be subverted to promote oncogenesis.…”
Section: Tip60-associated Proteins and Their Links To Cancermentioning
confidence: 99%
“…There are many reports of the histone acetyltransferases such as PCAF, p300/CBP and GCN5 acting as co-activators (Benkirane et al, 1998;Vassilev et al, 1998;Hamamori et al, 1999;Jiang et al, 1999;Masumi et al, 1999;Schiltz et al, 1999;Harrod et al, 2000;Lau et al, 2000a, b;Li et al, 2000;Trievel et al, 2000;Yamauchi et al, 2000;Vo and Goodman, 2001;Lang and Hearing, 2003;Patel et al, 2004). A number of transcriptional factors associate with p300/CBP, originally known as the global co-activator, and with PCAF and GCN5.…”
Section: Introductionmentioning
confidence: 99%